Physicochemical characterization of lime and cement stabilized clayey soils contaminated by heavy metals - Saeed, Khitam Abdulhussein (2014)
The presence of contaminated soils due to industrials and mining activities is a major concern in today’s heavily industrialized world. The contaminants lead to poor engineering properties for these soils. However, the effect of these contaminants on the geotechnical properties of clayey soils can be altered through chemical stabilization using traditional stabilizers, which result in achieving suitable material for construction purposes. On the other hand, the studies on the evaluation of microstructural, molecular, and leaching characteristics of treated contaminated clay soils are so limited. In this research, two contaminated tropical soils (mixed with different percentages of heavy metals) comprised mainly of kaolinite mineral i.e., Brown Kaolin and Laterite Clay. Similar contents of lime and cement (5% and 10% of dry weight) have been used for the stabilization process of contaminated clay soils. Two selected heavy metals Cu and Zn were chosen as nitrates to investigate their effects with time on the characteristics of the treated soils. The changes in the mineralogy, morphology and soil molecular structure due to the effect of stabilizers and heavy metals were explained based on X-ray Diffractometry (XRD), Energy Dispersive X-ray Spectrometry (EDAX), Field Emission Scanning Electron Microscopy (FESEM), Fourier Transform Infrared Spectroscopy (FTIR), Cation Exchange Capacity (CEC) and Brunauer Emmett and Teller (BET) surface area analysis. Leaching tests were also performed on cured contaminated samples, in order to investigate the potential of lime and cement stabilization technique to immobilize the heavy metals. The strength and compressibility of the stabilised soils with the effect of heavy metals were tested using unconfined compression and one dimensional consolidation tests. Based on the micro-structural characterization, strength and compressibility characteristics of the stabilized soils, cement was the most effective stabilizer than lime in terms of improving the strength and compressibility of contaminated treated soils. However, the heavy metals have more retarded effect on the cement treated samples than lime. This was due to precipitation of the metals onto the surface of calcium and aluminium silicates as insoluble hydroxides or sulphates. Thus, these compounds form an impermeable coating that acts as a barrier to inhibit cement hydration by impending transport of water into cement grain. Nevertheless, in the case of lime treatment, the metals ions adsorb and held as an amorphous mass in the pore spaces between the flocculated particles of treated samples. The pH values of leachate from all stabilized contaminated samples were found to be alkaline, indicating that the heavy metals were adsorbed on the surface of the cementations minerals. Finally, it can be concluded that the mechanical and the physico-chemical behaviours of the compacted specimens, as determined during testing, formed the basis for evaluating both the degree of immobilization of the heavy metal in the soil matrix, and the potential for rehabilitation of contaminated sites.